PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN TETAP DI PT PERTAMINA PATRA NIAGA JAKARTA SELAMA WORK FROM HOME - Nabil Azka Razzaq (2021)
This research is a quantitative research that aims to determine the Influence of work motivation and work discipline on job satisfaction of Permanent Employees of PT Pertamina Patra Niaga Jakarta during work from home. The population in this study were all employees permanent of PT Pertamina Patra Niaga Jakarta, totaling 227 employees. The number of samples used in this study were 70 employees using the slovin formula. The data used in this study is primary data, namely by distributing questionnaires. The data analysis technique used in this research is quantitative data analysis technique using statistical methods. The statistical method used is Partial Least Square (PLS). The test results show that (1) work motivation has a positive and significant effect on job satisfaction of employees of PT Pertamina Patra Niaga Jakarta during work from home, (2) work discipline has a positive and significant effect on job satisfaction of employees of PT Pertamina Patra Niaga Jakarta during work from home.